Roadmaps to Grace: Five Types of Lutheran Confessional Subscription - Samuelson, Erik T.R. (Dialog, 2006)
Though all pastors in North American Lutheran churches are expected to “subscribe” to the Lutheran Confessions, there are many different understandings as to what this means, each of which is tied to a particular understanding of the Lutheran Confessions themselves. Through the use of a methodological tool, the “Confessional Spectrum,” five approaches are presented. The author maintains that one of these approaches, “Roadmaps to Grace,” is the most helpful method for Lutheran Confessional theology in the 21st Century.